2015
DOI: 10.1097/jcn.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 2 Devices for Radial Artery Hemostasis After Transradial Coronary Intervention

Abstract: The application of the chitosan-based pad showed better hemostatic efficacy and a lower incidence of radial artery occlusion after transradial coronary intervention compared with the compression device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…In a previous study in which was evaluated hemostasis with use of the TR Band® device after radial puncture in patients with acute coronary syndrome and similar sociodemographic characteristics to this study, the incidence of hematoma was 3.4% (all type II) (1) . In another study, were compared two radial compression devices in patients after percutaneous coronary intervention, and was found that 20% of those using the TR Band® device presented minor bleeding (15) . Furthermore, the patients evaluated in our study underwent only a coronary diagnostic procedure, and generally, with a shorter duration than PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study in which was evaluated hemostasis with use of the TR Band® device after radial puncture in patients with acute coronary syndrome and similar sociodemographic characteristics to this study, the incidence of hematoma was 3.4% (all type II) (1) . In another study, were compared two radial compression devices in patients after percutaneous coronary intervention, and was found that 20% of those using the TR Band® device presented minor bleeding (15) . Furthermore, the patients evaluated in our study underwent only a coronary diagnostic procedure, and generally, with a shorter duration than PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized study with 600 participants, the use of a chitosan-based cushion with hemostatic properties, kept compressed on the site of the introducer after PCI, showed better hemostatic efficacy with less compression time (127.6 ± 33.0 minutes versus 181.6± 32.2; p < 0.001), and a lower incidence of RAO after 24 hours (5.4% versus 11.7%, p < 0.05), and after 30 days (5.0% versus 10.0%; p < 0.05) compared to the use of pneumatic wristbands ( 20 ) . It should be noted that the two types of compression were maintained for at least one hour until the first site evaluation.…”
Section: Discussionmentioning
confidence: 97%
“…Pancholy and colleagues reported RAO incidence of 4.4% at 24 h and 3.2% at 30 d using TR band in a cohort using 5F radial sheaths[ 8 ]. Dai et al[ 11 ] demonstrated that in post-transradial PCI patients, incidence of RAO was at least 11% at 24 h and 10% at 30 d. The study showed that air titration based compression strategy using TR band was superior to non-air titration strategies. However, the study utilized a non-specific, non-personalized method using manufacturer’s instructions.…”
Section: Discussionmentioning
confidence: 99%
“…While several compression bands and techniques tested have demonstrated a modest reduction in RAO, a more pragmatic and effective approach remains to be defined[ 11 ]. Therefore, we aimed to prospectively compare incidence of RAO between two conventional hemostatic compression devices (Safeguard Radial and TR band) using a pragmatic and novel air-inflation technique, in patients post-transradial PCI.…”
Section: Introductionmentioning
confidence: 99%